El clima durante el Plioceno en la region de Santa Maria Amajac, Hidalgo, Mexico - Aguilar, F.J.=700 1 Velasco De Leon, M.P.
(En, Es)
ilus., 45 ref.
Keywords: ANATOMIA DE LA PLANTA; HOJAS; CLIMA; MEXICO; PLIOCENO